Analisis Laporan Keuangan dalam Mengukur Kinerja Keuangan Perusahaan di Bursa Efek Indonesia : Studi Kasus pada PT. Unilever Indonesia, Tbk Periode 2019-2023 - Shafira Yumna Paramitha; Edi Wibowo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Unilever Indonesia, Tbk is one of the largest companies listed on the Indonesia Stock Exchange (BEI). The problem in this research is how the financial performance of PT. Unilever Indonesia, Tbk in 2019-2023 based on liquidity ratios, solvency ratios, activity ratios and profitability ratios. The purpose of this research is to analyze the performance conditions of PT. Unilever Indonesia, Tbk in 2019-2023 based on liquidity ratios, solvency ratios, activity ratios and profitability ratios. This research is a type of case study research at PT. Unilever Indonesia, Tbk for the 2019-2023 period. The type of data used is quantitative data. The data source used is secondary data, in the form of PT's balance sheet and profit and loss report. Unilever Indonesia, Tbk. The results of the liquidity ratio, an average current ratio of 61.75%, indicate quite good conditions. The average quick ratio is 41.86%, indicating unfavorable conditions. The average cash ratio is 5.37%, indicating unfavorable conditions. The results of the solvency ratio, the average debt to asset ratio is 77.11%, indicating very good conditions. The average debt to capital ratio is 3.39%, indicating unfavorable conditions. The activity ratio results show that the average fixed asset turnover ratio is 4.06 times, indicating unfavorable conditions. The average total asset turnover ratio is 2.14 times, indicating unfavorable conditions. The results of the profitability ratio, an average return on assets of 31.80%, indicate very good conditions. The average return on equity was 138.96%, indicating very good conditions. The average gross profit margin was 49.83%, indicating very good conditions. The average net profit margin is 14.78%, indicating good conditions.